Ectopic Pancreas at the Ampulla Diagnosed With Endoscopic Snare Papillectomy: A Case Report - Lefika Bathobakae MD, MPH; Derya Mücahit BS; Rammy Bashir MD, MSc; Joseph Russo MD; Angela Vidreiro MD; Nader Mekheal MD; Ruhin Yuridullah MD; Yana Cavanagh MD (SAGE Publishing, 2024)
Ectopic pancreas, also known as heterotopic pancreas, is a rare condition in which the pancreatic tissue is found outside its usual location in the gastrointestinal (GI) tract. It is commonly asymptomatic and benign, and is often discovered incidentally during routine imaging, endoscopy, surgery, or autopsy. However, complications can arise, such as inflammation, bleeding, obstruction, or even malignant transformation, necessitating surgical intervention in some cases. Ectopic pancreas at the ampulla of Vater (EPAV) is an extremely rare condition and a diagnostic and therapeutic nightmare. Most cases have been diagnosed through invasive surgery due to concerns for malignancy, which carries significant morbidity and mortality. In our case, endoscopic snare papillectomy (ESP) was employed to establish a diagnosis. Thus far, only one other case has been reported in which ESP was used to diagnose and resect a pancreatic heterotopia at the ampulla.